SHARIA INSURANCE COMPANY BUSINESS MANAGEMENT MODEL IN THE DIGITAL 4.0 ERA - Renny Oktavia; M. Taufiq (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2021)
This study aims to determine how the business management model of Islamic insurance companies in the digital era 4.0. The research method used is a qualitative research method using the Grounded Theory approach. The results of this study explain that, in running the insurance business in the era of revolution 4.0 implementing a supporting system, it is a combination of four components, namely: insurance / financial literacy, network marketing, human technology, and digital technology. The four components are driven by three mechanisms, namely: digital funneling, learning models, gamification systems, to achieve targeted business results. Keywords: Insurance Business, Sharia Insurance, Digital Technology